2008
DOI: 10.1038/aps.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of NYGGF4 inhibits glucose transport in 3T3-L1 adipocytes via attenuated phosphorylation of IRS-1 and Akt

Abstract: Aim: NYGGF4 is a novel gene that is abundantly expressed in the adipose tissue of obese patients. The purpose of this study was to investigate the effects of NYGGF4 on basal and insulin-stimulated glucose uptake in mature 3T3-L1 adipocytes and to understand the underlying mechanisms. Methods: 3T3-L1 preadipocytes transfected with either an empty expression vector (pcDNA3.1Myc/His B) or an NYGGF4 expression vector were differentiated into mature adipocytes. Glucose uptake was determined by measuring 2-deoxy-D-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…PID1 is highly expressed in the heart, suggesting a possible function for PID1 in cardiac disease. Previously studies indicated that PID1 acts directly on the IRS1/PI3K/AKT insulin pathway to reduce glucose uptake and transport and impairs mitochondrial function in adipose tissue [9]. Whether energy metabolism abnormality or mitochondrial dysfunction is thought to be tightly associated with the development of cardiac hypertrophy [10].…”
Section: Introductionmentioning
confidence: 99%
“…PID1 is highly expressed in the heart, suggesting a possible function for PID1 in cardiac disease. Previously studies indicated that PID1 acts directly on the IRS1/PI3K/AKT insulin pathway to reduce glucose uptake and transport and impairs mitochondrial function in adipose tissue [9]. Whether energy metabolism abnormality or mitochondrial dysfunction is thought to be tightly associated with the development of cardiac hypertrophy [10].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, research topics focus on the PID1 gene cloning, the relationship between PID1 and insulin resistance, and the underlying mechanism and signal pathways of its role in insulin resistance (Zhang et al 2009;Zhao et al 2010a,b;Man et al 2011;Wu et al 2011;Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive screening efforts also validated the interaction of PCLI1 with the cytosolic domain of LRP1, highlighting also the reduced expression of the gene in early Alzheimer's disease 3 . A series of studies, mainly based on the stable overexpression of PCLI1, led to the characterization of the function of the gene in signal transduction and insulin resistance [4][5][6] . Indeed, ectopic expression of its cDNA in 3T3-L1 pre-adipocytes or in skeletal myotubes reduced insulin-stimulated Tyr phosphorylation of IRS-1 and Ser phosphorylation of AKT, resulting in the inhibition of insulin-stimulated glucose uptake through attenuation of the PI3K signaling pathway.…”
Section: Introductionmentioning
confidence: 99%